Obesity is Associated with Increased Risk for Mortality Among Hospitalized Patients with COVID‐19. Issue 10 (25th August 2020) - Pettit, Natasha N.; MacKenzie, Erica L.; Ridgway, Jessica P.; Pursell, Kenneth; Ash, Daniel; Patel, Bhakti; Pho, Mai T.
Abstract : Objective: Obesity has been identified as a risk factor for severe coronavirus disease 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus 2 virus. This study sought to determine whether obesity is a risk factor for mortality among patients with COVID‐19. Methods: The study was a retrospective cohort that included patients with COVID‐19 between March 1 and April 18, 2020. Results: A total of 238 patients were included; 218 patients (91.6%) were African American, 113 (47.5%) were male, and the mean age was 58.5 years. Of the included patients, 146 (61.3%) had obesity (BMI > 30 kg/m 2 ), of which 63 (26.5%), 29 (12.2%), and 54 (22.7%) had class 1, 2, and 3 obesity, respectively. Obesity was identified as a predictor for mortality (odds ratio [OR] 1.7 [1.1‐2.8], P  =   0.016), as was male gender (OR 5.2 [1.6‐16.5], P  =   0.01) and older age (OR 3.6 [2.0‐6.3], P  <   0.0005). Obesity (OR 1.7 [1.3‐2.1], P  <   0.0005) and older age (OR 1.3 [1.0‐1.6], P  =   0.03) were also risk factors for hypoxemia. Conclusions: Obesity was found to be a significant predictor for mortality among inpatients with COVID‐19 after adjusting for age, gender, and other comorbidities. Patients with obesity were also more likely to present with hypoxemia.